Congenital vitamin D deficiency: presenting with feeding difficulty in early infancy: a case report - Mesfin Wubishet; Tesfa G. Meskel; Kibret Enyew (Journal of Medical Case Reports)
Abstract Background Vitamin D deficiency remains a significant public health concern, particularly among exclusively breastfed infants. Infants born to mothers with vitamin D deficiency, often influenced by cultural factors affecting diet, lifestyle, and clothing, are at increased risk of developing early and potentially fatal complications of hypocalcemic vitamin D deficiency. While seizures and tetany are well-recognized manifestations of hypocalcemia in infants, less common symptoms, such as feeding difficulties and recurrent apnea, are rarely documented. . Case presentation We present the case of a 50-day-old Ethiopian full-term infant, born to a Muslim Ethiopian mother, who experienced feeding difficulties, frequent brief episodes of apnea, and cyanosis since birth. The underlying cause was identified as hypocalcemia-induced laryngospasm due to congenital vitamin D deficiency, which resulted from maternal vitamin D deficiency. The mother, who has worn a niqab since childhood, had minimal sun exposure, contributing to her low vitamin D levels. The infant was successfully treated with intravenous calcium gluconate, followed by oral calcium and vitamin D supplementation, leading to complete resolution of symptoms and normalization of biochemical parameters. Conclusion Hypocalcemia-induced laryngospasm presenting with feeding difficulties and recurrent apneic episodes is a rare yet serious clinical condition. This report emphasizes the need to consider hypocalcemia as a potential cause of unexplained feeding difficulties or recurrent apnea in newborns and infants. Therefore, clinicians should remain vigilant and maintain a high index of suspicion to ensure timely diagnosis and treatment. It is essential to measure serum calcium and vitamin D levels in both the mother and infant, particularly for newborns of high-risk mothers, such as those who wear conservative religious clothing like a niqab. Furthermore, routine biochemical screening for vitamin D deficiency should be incorporated into antenatal care for all high-risk mothers, with appropriate supplementation to prevent potential complications in both mothers and their infants.